Comparison inventory of UNESCO World Heritage Villages: Kampung Morten, Melaka and ogimachi village, Shirakawa-Go, Gifu - Ab Rahman, Syakir Amir; Mahamod, Lukman Hakim; Nordin, Nurul Emmira Natasya; Rosli, Nur Syazwani; Mohamad Shokri, Nur Adila; Mohd Salleh, Nur Zafirah; Mohamad Pisol, Khairul Anuar; Ramlan, Abdul Aruf (UiTM Press, Universiti Teknologi MARA, 2020)
Heritage villages within UNESCO World Heritage Sites are often associated with natural, cultural and social characteristics of the urban and sub-urban fabric of the previous era. Kampung Morten, Melaka and Ogimachi Village, Shirakawa-go, Gifu each constitute important historical evidence in and of themselves. The villages have existed since the 11th century and each has a strong sense of community. Their traditional social systems and lifestyle customs have sustained the traditional houses and their associated historic environments. The integrity of the nominated areas in both villages is related to the presence of all the elements necessary to express their outstanding example of type of building, architectural or technological ensemble or landscape which illustrates their significant stages in human history. The villages have retained their authenticity; listed monuments and sites have been restored with appropriate treatments regarding design, materials, methodologies, techniques and workmanship, in accordance with conservation guidelines and principles. Thus, this paper seeks to understand and identify the characteristics of these historical villages by focusing on the use of traditional materials and techniques, as well as their viewpoints of setting, function, and UNESCO management systems.